Intestinal tuberculosis in a patient with end-stage renal disease on hemodialysis: A case report. Issue 32 (7th August 2020) - Lee, In Hee; Kim, Seong Gyu; Kwon, Joong Goo; Yang, Chun-Seok; Kang, Sungmin; Kim, Min-Kyung; Ahn, Dong Jik
Abstract: Rationale: Intestinal tuberculosis (TB) is rarely seen in patients with end-stage renal disease (ESRD). We report an intestinal TB case with a clinical presentation similar to that of colon cancer in a patient with ESRD on hemodialysis. Patient concerns: A 49-year-old man presented with a 3-month history of general weakness and anorexia. He had been treated for stage 5 chronic kidney disease (CKD) due to diabetic nephropathy for the last 3 years. His blood urea nitrogen and serum creatinine levels were 96.9 and 8.1 mg/dL, respectively, at the time of admission; azotemia was accompanied by severe anemia, hypoalbuminemia, hyperkalemia, and metabolic acidosis. Hemodialysis was initiated for suspected exacerbation of uremia; however, intermittent fever, night sweats, and abdominal discomfort persisted. Diagnoses: Abdominal computed tomography (CT) and whole-body 18 F-fluorodeoxyglucose positron emission tomography were indicative of ascending colon cancer with lymph node metastases. However, colonoscopy with biopsy revealed the formation of submucosal caseating granuloma and acid-fast bacillus. Interventions: We initiated quadruple therapy with isoniazid, rifampicin, pyrazinamide, and ethambutol. The patient continued the quadruple regimen for the first 2 months before switching to dual therapy and received anti-TB medications for a total of 12 months. Outcomes: After 9 months of standard anti-TB chemotherapy, polypoid residual lesions were noted during follow-up colonoscopy. Laparoscopy-assisted ileocecal resection was performed. No findings suggestive of recurrence of colonic TB were observed on follow-up abdominal CT at 6 months after discontinuation of anti-TB medications. Lessons: If non-specific uremic symptoms persist in patients with advanced CKD, the possibility of extrapulmonary TB such as intestinal TB must be considered. Also, in patients with radiologic suspicion of colon cancer, endoscopy with biopsy should be performed promptly to exclude colonic TB with similar clinical manifestations.